Pemanfaatan Aplikasi Mind Mapping Dalam Pembelajaran Pendidikan Agama Islam di SMP UBQ Nurul Islam Mojokerto - Andriansyah, Doni; Soraya, Irma (Yayasan Rahmat Islamiyah, 2024)
Education is a fundamental need for humans, because with education humans can develop physical and intellectual potential. Moreover, Islamic education, which is a guideline for Muslims in forming an obedient attitude and in accordance with religious law. Monotonous learning, namely using traditional learning methods, reduces the quality of education because it does not keep up with progress. However, the challenges in learning at UBQ Nurul Islam Mojokerto Middle School, the lack of asking students and outdated learning methods, make it necessary to innovate in learning, one of which is mind mapping. This research uses a quantitative approach to explain the application of mind mapping in PAI learning. The results show that this mindmapping method is quite well implemented by educators. Because by using the mind mapping method students become more active and make it easier for them to understand the learning.